Determinants of the Prevalence of Province Food Insufficiency in Indonesia in 2023 With A Quantile Regression Approach - Puja Ramdani, Ahmad; Murwiati, Asih (Lafadz Jaya Publisher, 2025)
This study analyzes the determinants of food insufficiency prevalence across 34 provinces in Indonesia using a quantile regression approach. The research focuses on three key variables: the Food Security Index (IKP), rice productivity (PVP), and per capita food expenditure (PPM), using 2023 cross-sectional data from Statistics Indonesia (BPS). Results from ordinary least squares (OLS) and quantile regression at the 25th, 50th, and 75th percentiles reveal that the Food Security Index has a consistent and significant negative effect on food insufficiency across all quantiles, with the strongest influence observed at the higher quantile (τ = 0.75). In contrast, rice productivity is not statistically significant at any quantile, while per capita food expenditure is only marginally significant at the 25th quantile. These findings suggest that improvements in food security contribute significantly to reducing food inadequacy, especially in regions with high prevalence rates. However, the impact of rice productivity and food spending varies across different segments, implying that context-specific policies are needed. The study recommends targeted government interventions to enhance food access, affordability, and regional food security equity.